Polatuzumab vedotin plus bendamustine and rituximab in patients with relapsed/refractory diffuse large B-cell lymphoma in the real world - Vodicka, Prokop; Benesova, Katerina; Janikova, Andrea; Prochazka, Vit; Belada, David; Mocikova, Heidi; Steinerova, Katerina; Duras, Juraj; Karban, Josef; Hanackova, Veronika; Sykorova, Alice; Obr, Ales; et al. (European journal of haematology, 2022)
OBJECTIVES: Polatuzumab vedotin with bendamustine and rituximab (Pola-BR) was approved for treatment of transplant-ineligible patients with relapsed/refractory DLBCL (R/R DLBCL). However, the number of patients treated in the GO29365 trial including the extension cohort was limited, and more data evaluating the efficacy of this treatment regimen is needed. METHODS: We analyzed 21 patients with R/R DLBCL to determine real-life efficacy and safety of Pola-BR regimen. Data of all patients entered the database of the NiHiL project (NCT03199066). RESULTS: Median overall survival was 8.7 months, and progression-free survival 3.8 months. The overall response rate was 33%. Grade 3-4 neutropenia was detected in 29%, thrombocytopenia in 38%, anemia in 19%, infections in 24% cases, and peripheral neuropathy in 5%. Discontinuation of treatment was caused by progression in 50%, adverse events in 31%, and intended bridging to CAR-T therapy in 19%. CONCLUSION: Although the outcome of patients is worse than in GO29365 trial, the use of Pola-BR regimen in the real world demonstrates tolerable toxicity profile and efficacy in transplant-ineligible patients with R/R DLBCL. Moreover, this regimen might represent a perspective option as a bridge to CAR-T therapy.
Keywords: Bendamustine Hydrochloride; polatuzumab vedotin; bendamustin hydrochlorid; Antibodies, Monoclonal; lidé; difúzní velkobuněčný B-lymfom; Rituximab; Antineoplastic Combined Chemotherapy Protocols; Lymphoma, Large B-Cell, Diffuse; DLBCL; protokoly protinádorové kombinované chemoterapie; real world; imunokonjugáty; nehodgkinský lymfom; Lymphoma, Non-Hodgkin; rituximab; monoklonální protilátky; Immunoconjugates; chimerické antigenní receptory; Receptors, Chimeric Antigen; Humans